From fragmentation to resilience: Connectivity and habitat diversity as drivers of fish persistence in California watersheds - Jeanette K. Howard; Analie R. Barnett; Kurt A. Fesenmyer; Mark G. Anderson (PLoS ONE, 2025)
This study evaluates how well key elements of freshwater resilience (e.g., hydrographic, physical habitat, and condition variables) explain the persistence of native fish species over time. Using the Temporal Beta Index (TBI), we quantify the change in fish species presence-absence in functionally connected networks within California to determine which watersheds within the network experienced significant changes in fish community composition. Random forest (RF) models were used to explore how the suite of network attributes influenced TBI and how the relationships varied by ecoregion. By integrating historical and contemporary fish distribution records with comprehensive datasets on fish passage barriers, stream habitat typologies, and watershed conditions, the analysis provides evidence that fragmentation—primarily driven by a century of dam construction—has impacted the persistence of fish species throughout the state. These results underscore the importance of maintaining and restoring interconnected river networks to preserve habitat heterogeneity, ensure the continued functionality of freshwater processes, and promote long-term ecological stability amidst ongoing and future environmental challenges. This research provides a framework to evaluate what factors contributed to fish loss in the past, thereby offering insights into enhancing the resilience of freshwater ecosystems and persistence of freshwater species into the future.